Emergence and functional fitness of memory CD4(+) T cells require the transcription factor Thpok - Ciucci, Thomas (Immunity, 2019)
Memory CD4(+) T cells mediate long term immunity, and their generation is a key objective of vaccination strategies. However, the transcriptional circuitry controlling the emergence of memory cells from early CD4(+) antigen-responders remains poorly understood. Here, using single-cell RNAseq to study the transcriptome of virus-specific CD4(+) T cells, we identified a gene signature distinguishing potential memory precursors from effector cells. We found that both that signature and the emergence of memory CD4(+) T cells required the transcription factor Thpok. We further demonstrated that Thpok cell-intrinsically protected memory cells from a dysfunctional, effector-like transcriptional program, similar to but distinct from the exhaustion pattern of cells responding to chronic infection. Mechanistically, Thpok bound genes encoding the transcription factors Blimp1 and Runx3, and acted by antagonizing their expression. Thus, a Thpok-dependent circuitry both promotes the differentiation and functional fitness of memory CD4(+) T cells, two previously unconnected critical attributes of adaptive immunity.